DEVELOPMENT OF 1D NUMERICAL MODEL FOR DAMBREAK SCOURING SIMULATION USING EXPLICIT FINITE DIFFERENCE METHOD - KURNIA AKBAR, INDIAN
This research will conduct a model simulation of the phenomenon of sediment transport due to Dambreak flow. The payment arrangement used in this study is the sale of Saint Venant – Exner. Completion of the arrangement will be divided into two agreements, namely Hydrodynamics and Morphodynamics agreements. Numerical simulation will be carried out using the Finite Difference discretization method. This discretization method was chosen as a comparison to previous studies, namely the Volume Difference Method. In finite different methods, the coefficients used are Forward, Backward, and Central Difference. This is found in numerical schemes such as FTCS (Forward Time Central Space), Leap Frog, Lax Wendroff, and Mac Cormack. So that the four numerical schemes will be chosen as the numerical scheme that will simulate the movable bed changes. The use of a numerical filter is also carried out as a shock capture which functions to maintain oscillations in the flow simulation. This was added externally because basically, Beda's discretization method doesn't have shock capture like Beda Volume. The four numerical schemes will be validated in laboratory experiments in previous studies by calculating the RMSE value. The simulation will be carried out until the capacity of the numerical scheme is obtained by calculating the Courant Number (CN) value.